Mortality and readmission following hip fracture surgery: a retrospective study comparing conventional and fast-track care. Issue 8 (29th August 2017) - Haugan, Kristin; Johnsen, Lars G; Basso, Trude; Foss, Olav A
Abstract : Objective: To compare the efficacies of two pathways—conventional and fast-track care—in patients with hip fracture. Design: Retrospective single-centre study. Setting: University hospital in middle Norway. Participants: 1820 patients aged ≥65 years with hip fracture (intracapsular, intertrochanteric or subtrochanteric). Interventions: 788 patients were treated according to conventional care from April 2008 to September 2011, and 1032 patients were treated according to fast-track care from October 2011 to December 2013. Primary and secondary outcome: Primary: mortality and readmission to hospital, within 365 days follow-up. Secondary: length of stay. Results: We found no statistically significant differences in mortality and readmission rate between patients in the fast-track and conventional care models within 365 days after the initial hospital admission. The conventional care group had a higher, no statistical significant mortality HR of 1.10 (95% CI 0.91 to 1.31, p=0.326) without and 1.16 (95% CI 0.96 to 1.40, p=0.118) with covariate adjustment. Regarding the readmission, the conventional care group sub-HR was 1.02 (95% CI 0.88 to 1.18, p=0.822) without and 0.97 (95% CI 0.83 to 1.12, p=0.644) with adjusting for covariates. Length of stay and time to surgery was statistically significant shorter for patients who received fast-track care, a mean difference of 3.4 days and 6 hours, respectively. There was no statistically significant difference in sex, type of fracture, age or Charlson Comorbidity Index score at baseline between patients in the two pathways. Conclusions: There was insufficient evidence to show an impact of fast-track care on mortality and readmission. Length of stay and time to surgery were decreased. Trial registration number: NCT00667914; results